Point spectrum in the equilibrium states of dynamic conflict systems and its role in the models of beliefs formation - Koshmanenko, V.; Satur, O. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
The structure of the point spectrum in the limit (in time) states of dynamic conflict systems is studied in terms of probability measures. It is shown that a necessary and sufficient condition for the appearance of measures with point spectra is a single priority strategy. In this case, we establish the exponential rate of concentration of the distributions with point spectrum and its density in the phase space. The possibility of using information about the structure of the point spectrum in a new mathematical model of the formation of the beliefs of individuals in an abstract society is proposed.